Risking NATO Testing the Limits of the Alliance in Afghanistan - Hoehn, Andrew R. (RAND Corporation, 2010)
NATO's success in Afghanistan--or lack thereof--will have significant implications for the alliance itself. The authors examine the current mission in light of NATO's history and with an eye toward the future. NATO faces a long and daunting list of issues that extends beyond the borders of the member countries. The alliance must confront them, however, because failure to do so would risk its long-term success and sustainability.